Digital silk road in the context of the people’s Republic of China - Alfiya Rafisovna Alikberova, Dmitriy Aleksandrovich Balakin (Opción, 2019)
The purpose of the article is the study and analysis of one of the components of OBOR - the Digital Silk Road in the context of the vision China foreign policy via the system-structural approach and comparative-comparative analysis. The main result of the study is the identification of new mechanisms of influence, features of the digital diplomacy of the PRC and the tools of soft power of China. Also, the conclusion was made that the Digital Silk Road project logically closes the Chinese initiative one belt - one road, girding the whole world with transport, economic, digital ways.